(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate some clinical and paraclinical characteristics of septic shock patients at Nghe An Friendship General Hospital in the period of 2023-2024. Method: A cross-sectional description study, data was collected on 103 patients diagnosed with septic shock at the Intensive Care Unit, Nghe An General Hospital from January 2023 to June 2024. Results: Of the 103 patients, men accounted for the majority (64.1%), the average age was 69.36 ± 12.54, the common age was over 60 years old with 78.6%; the common underlying diseases were hypertension (35%), diabetes (19.4%). The most common primary infection was respiratory with 47.6%, common symptoms were fever (93.2%), impaired consciousness (71%), leukocytosis (63.1%), increased hs-CRP with average concentration 146.2 ± 58.3 and pro-calcitonin 37.38 ± 45.4. Patients were in relatively severe condition with an average SOFA score of 8.78 ± 3.7. Conclusion: Patients with septic shock were hospitalized in relatively severe condition with a relatively high average SOFA score and were often found in elderly men with underlying diseases such as diabetes, cardiovascular disease with the common primary infection being respiratory; common symptoms were fever, leukocytosis and increased inflammatory markers.